2013
DOI: 10.1186/1746-1596-8-65
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the gastrointestinal NET grading system: Ki67 index criteria of the WHO 2010 classification is appropriate to predict metastasis or recurrence

Abstract: BackgroundIn the WHO 2010 classification, the neuroendocrine tumors (NETs) are subdivided by their mitotic index or Ki67 index into either G1 or G2 NETs. Tumors with a Ki67 index of <2% are classified as G1 and those with 3—20% are classified as G2. However, the assessment of tumors with Ki67 index of greater than 2% and less than or equal to 3% is still unclear. To resolve the problem, we validated the Ki67 index criteria of gastrointestinal NETs of the WHO 2010 classification.MethodsThe medical records of 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
(48 reference statements)
1
45
1
2
Order By: Relevance
“…However, none of our patients with G1/G2 and G2 NETs had lymph node metastasis (22). Only 1 of 12 (8.3%) patients had lymphatic or venous invasion, which is a low rate compared with that of other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…However, none of our patients with G1/G2 and G2 NETs had lymph node metastasis (22). Only 1 of 12 (8.3%) patients had lymphatic or venous invasion, which is a low rate compared with that of other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…8,57 Therefore, we additionally compared phospho-histone H3 data with Ki-67 values and found a very high correlation, with special reference to phospho-histone H3 manual counting. The impact of Ki-67 determination at the diagnostic level is however not well established in adrenocortical carcinoma, and from a practical point of view the value of this observation is limited.…”
Section: Impact Of Ki-67 Evaluation As Compared With Mitotic Count Inmentioning
confidence: 99%
“…Studies have shown the usefulness of this grading system, as some of the well-differentiated tumors with higher proliferative index (G2) seem to have worse prognosis than PanNET with lower proliferative index (G1) [6,7]. It has been shown that this grading system is a valid tool for progCorrespondence to: Jose Antonio Sousa Pereira; email: pereirajoseantonio@outlook.com nostic stratification in clinical practice and research [8,9]. The choice of treatment depends not only on the symptoms, stage of disease, degree of uptake of radionuclide but also on tumor grade [10].…”
mentioning
confidence: 99%